THE EFFECTIVENESS OF ONLINE LEARNING COMPARED TO TRADITIONAL EDUCATION - Khasanova Maftuna Ikhtiyorovna (Research Focus International Scientific Journal, 2025)
Online learning has revolutionized education by providing flexibility and accessibility. This paper examines its effectiveness compared to traditional education, focusing on cognitive, social, and emotional aspects. It explores the impact of digital tools, virtual classrooms, and multimedia resources on learning outcomes. Additionally, it discusses online assessment methods and student performance in both settings. The study concludes with recommendations for optimizing online and blended learning models.